Prevalence of primary and secondary dental dystrophies on a group of preschool and school-age children from Tîrgu-Mureş - Esian Daniela; Bica Cristina; Lazar Ana Petra; Stoica Oana ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2019)
Introduction: Pediatric Dentistry offers a completely different approach compared to that of adults especially in terms of patient cooperation, problems with growth and development and problems related to dental restoration in the context of a developing dentition.